Unexpected benefits of pre-university skills training for A-level students. Issue 1 (1st January 2017) - Jones, H. L.; Gaskell, E. H.; Prendergast, J. R.; Bavage, A. D.
Abstract: First-year undergraduates can find the transition from the prescriptive learning environment at school to one of self-directed learning at university, a considerable challenge. A Pre-university Skills Course (PSC) was developed to address this issue by preparing sixth formers for the university learning style. It was piloted with students in the year prior to A-level examinations at a selective state-funded school in East Anglia. The present paper examines the effect of the course on the students' A-level tariff. Chi-squared analysis of A-level grades of students with comparable GCSE results, indicate that students who undertook the PSC performed significantly better in their A-level results than those who did not. These data demonstrate how skills training might improve A-level performance and assist in the transition to university.